Internal and external factors of rice farming in the coastal area. Issue 1 (April 2020) - Saadah,; Amrullah, A; Darwis,; Ibrahim, T; Fudjaja, L; Bulkis, S; Dzulhajrah, A S; Wahyudi, D P
Abstract: This research aims to determine and described internal and external factors, which become the strengths, weaknesses, opportunities, and threats of rice farming in the coastal area of Maros Regency. A sampling of the study area was carried out by the census method by taking the entire population into a sample of 23 farmers who were members of the Pajalayya Baru Farmer Group and key informants as many as two people consisting of village officials and extension workers. The result of this research identifies that there were four aspects of internal and external factors that influenced the development of rice farming in Kurri Caddi, which were strengths, weaknesses, opportunities, and threats. The strengths consist of the available workers, cultivation land, farming experiences, farmer's productivity. The weaknesses consist of the lack of skills of the farmer, uncertified seed, unbalanced fertilizer use, bad-timing tillage, and farmers are reluctant to use new farming innovation. The opportunities consist of the emergence of new forms of employment, a group of farmers that provide the distribution of farming supports and facilities and strong community self-help. Threats consist of problems of road transportation facilities, attack of pests and diseases, Abrasion and erratic weather.